A move analysis of the discussion sections in English as a second language learners’ quantitative theses - Mary Joy V. Herediano; Riziel E. Secretario; Arnold M. Sumpo; Ivy F. Amante; Rovy M. Banguis; Gay Emelyn L. Lariosa; Norhanie D. Macarao (International Journal of Evaluation and Research in Education (IJERE), 2026)
Discussion section of research papers is one of the most essential sections because the authors demonstrate the knowledge contribution of their research findings to the existing literature. In this study, 16 quantitative theses analytical components written by the English language learners were gathered and analyzed. By utilizing qualitative research design focusing on move analysis, the researchers found out that Move 1 (background information), Move 2 (reporting results), Move 3 (summarizing the results), and Move 4 (commenting on the results) were identified as obligatory moves since they serve as the primary objectives of this explanatory segment. Move 6 (evaluating methodology) was recognized as a traditional move. Move 5 (summarizing the study) and Move 7 (deductions from the research) were noted as optional moves. Distinct linguistic characteristics and verbal signals were observed in the various moves, with the patterns of these steps identified as a structured arrangement in the results discussion. The results aim to help student writers recognize the rhetorical frameworks that should be included in the interpretive sections of quantitative theses.